Ventilation during cardiopulmonary resuscitation in the infant. Mouth to mouth and nose, or bag-valve-mask? A quasi-experimental study - Myriam Santos-Folgar; Martín Otero-Agra; Felipe Fernández-Méndez; María Teresa Hermo-Gonzalo; Roberto Barcala-Furelos; Antonio Rodríguez-Núñez (Elsevier, 2018)
Introduction: It has been observed that health professionals have difficulty performing quality cardiopulmonary resuscitation (CPR). The aim of this study was to compare the quality of ventilations performed by Nursing students on an infant model using different methods (mouth-to-mouth-and-nose or bag-valve-mask). Material and methods: A quasi-experimental cross-sectional study was performed that included 46 second-year Nursing students. Two quantitative 4-min tests of paediatric CPR were performed: (a) mouth-to-mouth-and-nose ventilations, and (b) ventilations with bag-valve-mask. A Resusci Baby QCPR Wireless SkillReporter® mannequin from Laerdal was used. The proportion of ventilations with adequate, excessive, and insufficient volume was recorded and analysed, as well as the overall quality of the CPR (ventilations and chest compressions). Results: The students were able to give a higher number of ventilations with adequate volume using the mouth-to-mouth-and-nose method (55 ± 22%) than with the bag-valve-mask (28 ± 16%, p < .001). The overall quality of the CPR was also significantly higher when using the mouth-to-mouth-and-nose method (60 ± 19 vs. 48 ± 16%, p < .001). Conclusions: Mouth-to-mouth-and-nose ventilation method is more efficient than bag-valve-mask ventilations in CPR performed by nursing students with a simulated infant model. Resumen: Introducción: Se ha observado que los profesionales sanitarios tienen dificultades para realizar maniobras de reanimación cardiopulmonar (RCP) de calidad. Nuestro objetivo ha sido comparar la calidad de las ventilaciones en un modelo de lactante según el método utilizado (boca a boca y nariz o bien bolsa autoinflable y mascarilla facial) por estudiantes de Enfermería. Material y métodos: Estudio cuasiexperimental de corte transversal que incluyó a 46 estudiantes de Enfermería de segundo curso. Se realizaron 2 pruebas cuantitativas de RCP pediátrica de 4 min: a) con ventilación boca a boca y nariz; b) con ventilación con bolsa autoinflable y mascarilla facial. Se utilizó un maniquí Resusci Baby QCPR Wireless SkillReporter® de Laerdal. Se registraron y analizaron los porcentajes de ventilaciones con volumen adecuado, excesivo e insuficiente, además de la calidad global de la RCP (ventilaciones y compresiones torácicas). Resultados: Los estudiantes consiguieron dar más ventilaciones con volumen apropiado con el método boca a boca y nariz (55 ± 22%) que con bolsa y mascarilla (28 ± 16%; p < 0,001). La calidad global de la RCP también fue significativamente superior cuando aplicaron el método boca a boca y nariz (60 ± 19 vs. 48 ± 16%; p < 0,001). Conclusiones: La ventilación boca a boca y nariz es más eficiente que la ventilación con bolsa autoinflable y mascarilla facial en la RCP realizada por estudiantes de Enfermería con un modelo simulado de lactante.